Ferritic stainless steel with improved strength, workability and corrosion resistance.
Optimized alloy compositions in ferritic stainless steel, particularly through controlled Si and Cr contents, address the balance of strength, workability, and corrosion resistance, achieving desired mechanical properties and cost-effectiveness.
Patent Information
- Application Number
- JP2023530070
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-19
- Filing Date
- 2021-08-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-08-26
AI Technical Summary
Existing ferritic stainless steels face challenges in achieving a balance of low cost, high strength, good workability, and improved corrosion resistance, particularly in high-strength grades like STS 430, where adding stabilizing elements like Ti and Nb either increases cost or reduces strength.
A ferritic stainless steel composition with controlled amounts of C, N, Si, Cr, and Ti, optimized through formulas (1) and (2), ensuring a tensile strength of 470 MPa or more, a stretching ratio of 27% or more, and a pitting potential of 150 mV or more, while reducing raw material costs by adjusting Si and Cr contents.
The solution provides a ferritic stainless steel with enhanced strength, workability, and corrosion resistance, achieving desired mechanical properties and cost-effectiveness by optimizing alloy compositions.
Smart Images

Figure 0007607766000003 
Figure 0007607766000004 
Figure 0007607766000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel having improved strength, workability and corrosion resistance, and more particularly to a ferritic stainless steel having low cost and improved strength, workability and corrosion resistance. [Background technology]
[0002] Ferritic stainless steel has beautiful surface quality and is cheaper than austenitic stainless steel, so it is used in a variety of industrial fields, including washing machines, refrigerators, and various home appliances. Recently, with the increasing demand for premium home appliances, there is a growing demand for ferritic stainless steels with higher corrosion resistance and strength. At the same time, there is also a demand for cost reduction, so the development of steel materials that can satisfy this demand is necessary.
[0003] In order to be applicable to a wide range of industrial fields, they must be processed into complex shapes. In general, when strength is improved through the solid solution strengthening effect, there is a risk of deterioration in workability, so appropriate alloy design is required to ensure sufficient strength and workability.
[0004] In addition, the existing high-strength ferritic stainless steel, STS 430, has high strength but low corrosion resistance due to its high C and N content and lack of stabilizing elements such as Ti and Nb. Some steels have improved corrosion resistance by lowering the C and N content and adding Ti or Nb, but adding expensive Nb increases the price, while adding Ti reduces the price increase but reduces the strength, making it difficult to meet the required strength. Therefore, it is necessary to develop a ferritic stainless steel that has low cost, as well as improved corrosion resistance, strength, and workability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Korean Patent Publication No. 10-2010-0075190 Summary of the Invention [Problem to be solved by the invention]
[0006] In order to solve the above problems, the present invention provides a ferritic stainless steel having low cost and improved strength, workability and corrosion resistance. [Means for solving the problem]
[0007] As a means for achieving the above-mentioned object, a ferritic stainless steel according to one example of the present invention may consist, by weight percentage, of C: 0.0005-0.02%, N: 0.005-0.02%, Si: 0.7-1.0%, Cr: 16.0-17.0%, Ti: 0.05-0.3%, with the remainder being Fe and unavoidable impurities, and may have a value of the following formula (1) of 21 or more and 25 or less, a tensile strength of 470 MPa or more, and an elongation of 27% or more. (1)7*Si+Cr In the formula (1), Si and Cr represent the content (wt %) of each element. In each of the ferritic stainless steels of the present invention, the value of the following formula (2) may be 20 or more, and the pitting potential value may be 150 mV or more. (2)Cr+4*Si+0.1*Ti / (C+N) In the formula (2), Cr, Si, Ti, C, and N represent the content (wt%) of each element. Effect of the Invention
[0008] According to an embodiment of the present invention, a ferritic stainless steel having low cost and improved strength, workability and corrosion resistance can be provided through designing the alloy composition. According to the present invention, Si is added upward and the amount of Cr added is reduced, thereby reducing the raw material cost. According to the present invention, strength and workability can be improved through new composition parameters in which Si is added upward and Si and Cr contents are adjusted. The ferritic stainless steel according to one embodiment may have a tensile strength of 470 MPa or more and an elongation of 27% or more. According to the present invention, the corrosion resistance can be improved through new composition parameters that adjust the contents of Si, Cr, Ti, C, and N. The ferritic stainless steel according to one embodiment may have a pitting potential value of 150 mV or more. A preferred embodiment of the ferritic stainless steel may have a tensile strength of 470 MPa or more, an elongation of 27% or more, and a pitting potential value of 150 mV or more. [Brief description of the drawings]
[0009] [Figure 1] 1 is a graph showing the tensile strength values of each example according to formula (1). [Diagram 2] 1 is a graph showing the elongation ratio values of each example according to formula (1). [Diagram 3] 1 is a graph showing pitting potential values of each example according to formula (2). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The ferritic stainless steel of the present invention may contain, by weight, C: 0.0005-0.02%, N: 0.005-0.02%, Si: 0.7-1.0%, Cr: 16.0-17.0%, Ti: 0.05-0.3%, with the remainder being Fe and unavoidable impurities, and may have a value of the following formula (1) that is 21 or more and 25 or less, a tensile strength of 470 MPa or more, and an elongation of 27% or more. (1)7*Si+Cr In the formula (1), Si and Cr represent the content (wt %) of each element.
[0011] In the following, preferred embodiments of the present invention will be described. However, the embodiments of the present invention may be modified into various other forms, and the technical concept of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art. The terms used in this application are only used to describe specific examples. For example, singular expressions include plural expressions unless the context clearly requires the singular. In addition, it should be noted that the terms "comprise" or "comprise" used in this application are used to clearly indicate the presence of features, steps, functions, components, or combinations thereof described in the specification, and are not used to preliminarily exclude the presence of other features, steps, functions, components, or combinations thereof. Meanwhile, unless otherwise defined, all terms used herein should be considered to have the same meaning as that commonly understood by a person having ordinary skill in the art to which the present invention belongs. Therefore, unless clearly defined herein, specific terms should not be interpreted as having an overly ideal or formal meaning. For example, in this specification, singular expressions include plural expressions unless there is a clear exception in the context. In addition, in this specification, the terms "about," "substantially," and the like are used in the sense of a numerical value or close to a numerical value when the tolerances of manufacturing and materials inherent in the referred meaning are presented, and are used to prevent unconscionable infringers from unfairly exploiting the disclosure in which precise or absolute numerical values are referred to in order to aid in the understanding of the present invention.
[0012] The existing high-strength ferritic stainless steel for home appliances, STS 430, has a problem of low corrosion resistance, and when Nb is added to improve the corrosion resistance, the cost increases, and when Ti is added, the strength decreases. In order to solve these problems, the inventors have studied in depth how to improve the strength and corrosion resistance while reducing the cost. As a result, they have confirmed that the above problems can be solved by controlling the contents of alloy components Si, Cr, Ti, C, and N based on the composition system of ferritic stainless steel with Ti added, using a compositional relationship, and have completed the present invention.
[0013] The ferritic stainless steel of the present invention may contain, by weight, C: 0.0005-0.02%, N: 0.005-0.02%, Si: 0.7-1.0%, Cr: 16.0-17.0%, Ti: 0.05-0.3%, with the remainder being Fe and unavoidable impurities.
[0014] The reasons for limiting the range of each alloying element will be explained below. The C content may be 0.0005 to 0.02% by weight. If the C content is less than 0.0005 wt%, the refining cost for producing a high-purity product becomes high, and if the C content exceeds 0.02 wt%, there is a problem that the impurities in the material increase, resulting in a decrease in elongation rate and corrosion resistance. In order to improve the elongation rate and corrosion resistance, the C content may be preferably 0.01 wt% or less. The N content may be 0.005 to 0.02% by weight. If the N content is less than 0.005 wt%, the crystallization of TiN is reduced, resulting in a decrease in the equiaxed crystal ratio of the slab, while if the N content exceeds 0.02 wt%, the impurities in the material increase, resulting in a decrease in the elongation rate and corrosion resistance. In order to improve the elongation rate and corrosion resistance, the N content may be preferably 0.015 wt% or less.
[0015] The Si content may be 0.7 to 1.0% by weight. The existing STS 430 steel grade has a low Si content of 0.3-0.6 wt%, but in the present invention, the Si content is increased to the range of 0.7-1.0 wt% to ensure strength and corrosion resistance. If the Si content is less than 0.7 wt%, the amount of solid solution of Si is insufficient, resulting in a decrease in tensile strength and corrosion resistance, and if the Si content exceeds 1.0 wt%, there is a problem that the strength of the material increases excessively and the elongation rate decreases. In order to improve strength and corrosion resistance, the Si content can be more preferably controlled to the range of 0.8-1.0 wt%. In this case, the target Si content may be 0.9 wt%. The stainless steel of the present invention has improved corrosion resistance due to the increased Si content compared to the existing steel type STS 430. The pitting potential of STS 430 steel is 145 mV or less, but the ferritic stainless steel of the present invention has a pitting potential of 150 mV or more, and can also ensure a pitting potential of 160 mV or more.
[0016] The Cr content may be 16.0 to 17.0 wt %. If the Cr content is less than 16.0 wt%, it is difficult to secure sufficient corrosion resistance and strength, and if the Cr content exceeds 17.0 wt%, there is a problem of a large burden of price increase. The Cr content of the existing STS 430 steel type is also in the range of 16.0 to 17.0 wt%, but it is necessary to contain 16.7 wt% or more of Cr to secure corrosion resistance. However, in the present invention, since the corrosion resistance and strength can be improved by increasing the Si content, the Cr content can be limited to 16.5% or less, and the manufacturing cost can be further reduced. Therefore, the preferred Cr content may be 16.0 to 16.5 wt%. The Cr content may more preferably be 16.1 to 16.3 wt%. The Ti content may be 0.05 to 0.3% by weight. If the Ti content is less than 0.05 wt%, the dissolved C and N elements cannot be sufficiently fixed, resulting in a problem of reduced corrosion resistance, and if the Ti content exceeds 0.3 wt%, defects due to Ti-based inclusions will increase. For the purpose of improving corrosion resistance, the Ti content may be preferably 0.18 to 0.25 wt%.
[0017] The remaining component of the present invention is iron (Fe). However, in a normal manufacturing process, unintended impurities may be inevitably mixed in from the raw materials or the surrounding environment, and it is not possible to exclude them. Since any engineer of a normal manufacturing process would know about these impurities, the contents of all of them will not be mentioned in this specification. Among the alloy compositions mentioned above, Si and Cr are elements that are closely related to the corrosion resistance, strength, and workability of ferritic stainless steel. Si and Cr are elements that strengthen the passive film of ferritic stainless steel to improve corrosion resistance, and at the same time, are dissolved in the matrix to improve strength. However, since Si and Cr are elements that reduce workability, it is necessary to understand the correlation between each element and the material in order to derive the optimal composition.
[0018] With this in mind, the inventors of the present invention have studied the correlation of alloy composition for improving tensile strength and elongation within the above-mentioned alloy composition, and have derived that when the value of the following formula (1) is 21 or more and 25 or less, a tensile strength of 470 MPa or more and an elongation of 27% or more can be achieved. (1)7*Si+Cr In the formula (1), Si and Cr represent the content (wt %) of each element. If the value of formula (1) is less than 21, the solid solution strengthening effect of Si and Cr is not fully exerted, making it difficult to ensure a tensile strength of 470 MPa or more. On the other hand, if the value of formula (1) exceeds 25, workability decreases and it becomes difficult to ensure an elongation rate of 27% or more.
[0019] In addition, the present inventors have studied the correlation between the contents of Ti, C, and N as well as the contents of Si and Cr and corrosion resistance in order to improve corrosion resistance. C forms Cr carbide at grain boundaries in areas that have been thermally affected by heat treatment, etc., and the Cr concentration decreases and depletion occurs around the Cr carbide, which can induce intergranular corrosion. Ti fixes C and N to form Ti(C,N) carbonitrides, which are more stable than Cr carbides, thereby suppressing Cr precipitation and improving corrosion resistance. With this in mind, the inventors of the present invention have studied the correlation of alloy compositions for improving corrosion resistance within the above-mentioned alloy compositions, and have derived that when the value of the following formula (2) is 20 or more, a pitting potential of 150 mV or more can be achieved. (2)Cr+4*Si+0.1*Ti / (C+N) In the formula (2), Cr, Si, Ti, C, and N represent the content (wt%) of each element. If the value of formula (2) is less than 20, sufficient corrosion resistance is not ensured and it is difficult to ensure a pitting potential of 150 mV or more.
[0020] The present invention will be described in more detail with reference to the following examples. However, it should be noted that the following examples are merely for illustrating and explaining the present invention in more detail, and are not intended to limit the scope of the present invention, as the scope of the present invention is determined by the matters described in the claims and matters reasonably inferred therefrom.
[0021] <Example> A steel having the composition shown in Table 1 below was produced in the form of a slab through continuous casting, which was then hot-rolled at 800 to 1250°C, annealed, cold-rolled, and finally annealed at 800 to 950°C to produce a ferritic stainless steel sheet as a final cold-rolled product. The values in formulas (1) and (2) in Table 1 are values derived by substituting the composition in Table 1 for the values in formulas (1) and (2) described in this specification. The cold-rolled products were processed by JIS13B test pieces at 90° to the rolling direction to measure the tensile strength (MPa) and elongation (%) at room temperature. The surface of the material was polished with #600 and then the pitting potential (E pit The measurement results are summarized in Table 2.
[0022] [Table 1]
[0023] [Table 2]
[0024] Referring to Tables 1 and 2, it can be seen that the alloy compositions and formula (1) values defined in the present invention and the values of formula (1) of 21 or more result in a tensile strength of 470 MPa or more, and that the values of formula (1) of 25 or less result in an elongation of 27% or more. It can also be seen that the values of formula (2) of 20 or more result in a pitting potential of 150 mV or more. It can also be seen that when the values of formula (1) of 21 to 25 and the values of formula (2) of 20 or more are all satisfied, the tensile strength of 470 MPa or more, the elongation of 27% or more, and the pitting potential of 150 mV or more are all satisfied.
[0025] On the other hand, in the steels A and B of the comparative examples, the Si content did not reach 0.7 wt%, which is the lower limit of the Si content defined in the present invention, and the value of formula (1) was less than 21, and the value of formula (2) was less than 20. As a result, the elongation was high at 30% or more, but the tensile strength was less than 470 MPa, and the pitting potential value was less than 150 mV.
[0026] In the comparative steel type C, the Cr content did not reach 16.0 wt%, which is the lower limit of the Cr content limited by the present invention, and the value of formula (1) was less than 21 and the value of formula (2) was less than 20. As a result, the elongation ratio was high at 30% or more, but the tensile strength was less than 470 MPa and the pitting potential value was less than 150 mV. In the comparative steels D and E, the Si content exceeded 1.0 wt%, which is the upper limit of the Si content defined by the present invention, and the value of formula (1) exceeded 25. As a result, the tensile strength was 470 MPa or more, but the elongation was less than 27%. In the comparative steel type F, the Ti content did not reach 0.05 wt%, which is the lower limit of the Ti content defined in the present invention, and the value of formula (2) was less than 20. As a result, the tensile strength was 470 MPa or more and the elongation was 27% or more, but the pitting potential value was less than 150 mV.
[0027] The attached Figures 1, 2, and 3 are graphs that visualize the above results. Figure 1 is a graph showing the tensile strength values of each example according to the value of formula (1). It can be seen from Figure 1 that when the value of formula (1) is 21 or more, a tensile strength of 470 MPa or more can be ensured. However, from Figure 2, it can be seen that in the comparative example steel types D and E, which satisfy the value of formula (1) of 21 or more and have a tensile strength of 470 MPa or more, the value of formula (1) exceeds 25 and the elongation rate is less than 27%. Fig. 3 is a graph showing the pitting potential values of each example according to the value of formula (2). It can be seen from Fig. 3 that when the value of formula (2) is 20 or more, a pitting potential of 150 mV or more can be ensured.
[0028] Although exemplary embodiments of the present invention have been described above, the present invention is not limited thereto, and it should be understood that various changes and modifications can be made by those skilled in the art without departing from the concept and scope of the following claims. [Industrial Applicability]
[0029] According to the present invention, it is possible to provide a ferritic stainless steel with reduced cost by adjusting the contents of Si and Cr. In addition, it is possible to provide a ferritic stainless steel with improved strength, workability, and corrosion resistance through composition parameters. Therefore, it can be used in various industrial fields such as various home appliances.
Claims
[Claim 1] The alloy contains, by weight, C: 0.0005-0.02%, N: 0.005-0.02%, Si: 0.7-1.0%, Cr: 16.0-17.0%, Ti: 0.05-0.3%, and the remainder being Fe and unavoidable impurities; The value of the following formula (1) is 21 or more and 25 or less, and the value of the following formula (2) is more than 20, A ferritic stainless steel characterized by having a tensile strength of 470 MPa or more, an elongation of 27% or more, and a pitting potential value of 150 mV or more. (1) 7*Si+Cr (2) Cr+4*Si+0.1*Ti / (C+N) (In the formulas (1) and (2), Si, Cr, Ti, C, and N represent the contents (wt%) of each element.)
Citation Information
Patent Citations
Ferrite stainless steel for automobile exhaust emission system and manufacturing method thereof
CN101962740A
Medium-chromium ferrite stainless steel and manufacturing method thereof
CN102690994A
Ferritic stainless steel sheet for coating and painted steel sheet
JP2020164955A
Method for manufacturing ferrite stainless steel sheet with excellent surface property
KR1020100075190A